Hearing abilities and sound reception of broadband sounds in an adult Risso’s dolphin (Grampus griseus) - Mooney, T.; Yang, W.; Yu, H.; Ketten, Darlene; Jen, I. (Springer, 2015)
© 2015, Springer-Verlag Berlin Heidelberg. While odontocetes do not have an external pinna that guides sound to the middle ear, they are considered to receive sound through specialized regions of the head and lower jaw. Yet odontocetes differ in the shape of the lower jaw suggesting that hearing pathways may vary between species, potentially influencing hearing directionality and noise impacts. This work measured the audiogram and received sensitivity of a Risso’s dolphin (Grampus griseus) in an effort to comparatively examine how this species receives sound. Jaw hearing thresholds were lowest (most sensitive) at two locations along the anterior, midline region of the lower jaw (the lower jaw tip and anterior part of the throat). Responses were similarly low along a more posterior region of the lower mandible, considered the area of best hearing in bottlenose dolphins. Left- and right-side differences were also noted suggesting possible left–right asymmetries in sound reception or differences in ear sensitivities. The results indicate best hearing pathways may vary between the Risso’s dolphin and other odontocetes measured. This animal received sound well, supporting a proposed throat pathway. For Risso’s dolphins in particular, good ventral hearing would support their acoustic ecology by facilitating echo-detection from their proposed downward oriented echolocation beam.